Letter from Robert S. Mulliken to Harrison Shull, 1962 - Mulliken, Robert Sanderson (1962)
Letter between Robert S. Mulliken and Harrison Shull, American quantum chemists, concerning the work of Dr. Roberto Moccia, who Mulliken persuaded to stay at the University of Chicago for the summer and to apply for attendance to the Gordon Research Conference.
Keywords: Shull, Harrison; Mulliken, Robert Sanderson; Gordon Research Conferences; Moccia, Roberto; Quantum chemistry; Nobel Prize winners; Physicists; Chemists